Contributions of ichnology to palaeoecology, palaeogeography, and sedimentology. A special issue related to the Second Latin-American Symposium on Ichnology (SLIC 2013) - Melchor, Ricardo Nestor (2015)
Fil: Melchor, Ricardo Nestor. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Ciencias de la Tierra y Ambientales de La Pampa. Universidad Nacional de La Pampa. Facultad de Ciencias Exactas y Naturales. Instituto de Ciencias de la Tierra y Ambientales de La Pampa; Argentina